Computational Optimizing the Electromagnetic Wave Reflectivity of Double‐Layered Polymer Nanocomposites. Issue 4 (11th February 2022) - Wei, Linfeng; Ma, Jianzhong; Ma, Li; Zhao, Chongxiang; Xu, Menglong; Qi, Qing; Zhang, Wenbo; Zhang, Lei; He, Xiang; Park, Chul B.
Abstract: Double‐layered absorption‐dominated electromagnetic interference (EMI) shielding composites are highly desirable to prevent secondary electromagnetic wave pollution. However, it is a tremendous challenge to optimize the shielding performance via the trial‐and‐error method due to the low efficiency. Herein, a novel approach of computation‐aided experimental design is proposed to efficiently optimize the reflectivity of the double‐layered composites. A normalized input impedance (NII) method is presented to calculate the electromagnetic wave reflectivity of multilayered EMI shielding composites. The calculated results are a good match with the experimental results. Then, the NII method is utilized to design polyvinylidene difluoride/MXene/carbon nanotube (PVDF/MXene/CNT) composites. According to the optimization of the NII method, the prepared PVDF/MXene/CNT composite has an ultralow reflectivity of 0.000057, which outperforms that reported in current work and satisfies the requirement of electromagnetic wave absorbing material. Additionally, its average EMI shielding effectiveness is 30 dB, demonstrating that PVDF/MXene/CNT composite simultaneously achieves shielding and absorption. The ultralow reflection mechanism can be ascribed to the ideal impedance match. Both the PVDF/MXene and the PVDF/CNT layers can attenuate electromagnetic energy, which subverts the traditional cognition of double‐layered absorption‐dominated EMI shielding composites. The NII method opens a way for the practical fabrication of double‐layered absorption‐dominated EMI shielding composites. Abstract : A normalized input impedance (NII) method is proposed to calculate the electromagnetic wave reflectivity of multilayered electromagnetic interference shielding composites, thus optimizing the layer composition. By the design of the NII method, the as‐prepared double‐layered polyvinylidene difluoride/MXene/carbon nanotube (PVDF/MXene/CNT) composite shows an ultralow reflectivity. The absorption‐dominated shielding mechanism can be ascribed to the high absorption capacity of PVDF/MXene and PVDF/CNT.